2019
DOI: 10.1093/tas/txz076
|View full text |Cite
|
Sign up to set email alerts
|

Birth weight threshold for identifying piglets at risk for preweaning mortality

Abstract: Abstract Several studies have suggested there is a critical relationship between piglet birth weight and preweaning mortality. Thus, the objective of the current work was to identify a birth weight threshold value for preweaning mortality. Birth weight and survival data from two studies involving a combined total of 4,068 piglets from 394 litters on four commercial farms (three European, one U.S.) were compiled for a pooled, multistudy analysis. Overall preweanin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 23 publications
(42 reference statements)
6
50
0
3
Order By: Relevance
“…The average number of piglets born alive per litter (11.5 to 12.4) was similar to that for U.S. herds reported by PigChamp at the time this study was carried out (13.2 piglets per sow; 2017, 2018). Average piglet weights (1.41 to 1.44 kg) were similar to those reported in recent commercial studies (e.g., Vasdal et al, 2011 ; Feldpausch et al, 2019 ).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The average number of piglets born alive per litter (11.5 to 12.4) was similar to that for U.S. herds reported by PigChamp at the time this study was carried out (13.2 piglets per sow; 2017, 2018). Average piglet weights (1.41 to 1.44 kg) were similar to those reported in recent commercial studies (e.g., Vasdal et al, 2011 ; Feldpausch et al, 2019 ).…”
Section: Resultssupporting
confidence: 85%
“…A major factor associated with this increase is the reduction in average piglet birth weight due to the increase in litter sizes that have occurred in commercial dam lines over a similar time period (PigChamp, 2019). Estimates suggest that approximately 10 to 15% of piglets born are of low birth weight (i.e., weighing <1 kg) and that mortality in these piglets is extremely high, often exceeding 50% ( Feldpausch et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Poor development of the GIT of IUGR pigs persists pre-and post-weaning (D'Inca et al, 2011;Dong et al, 2014), with reduced rate of GIT maturation thought to negatively affect performance (Wang et al, 2005). LBW pigs represent a considerable economic problem to pig producers as a result of increased morbidity and mortality (Hales et al, 2013;Ferrari et al, 2014;Feldpausch et al, 2019), higher propensity to develop enteric health problems, poorer feed efficiency as well as carcase yield and quality with increased adiposity (Rehfeldt et al, 2008;D'Inca et al, 2011;Nissen and Oksbjerg, 2011;Zhang et al, 2018). However, a proportion of LBW pigs exhibit compensatory growth within the same environment as those who remain stunted (Paredes et al, 2012;Douglas et al, 2013;Huting et al, 2018), although an explanatory mechanism for this phenomenon is yet to be proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Piglets with low birth weight less than 1.13 kg are at risk of lower survival rate and longer time to market [ 14 ]. Previous study has proposed the relationship between birth weight and survival rate for piglets, when increased birth weight class by 100, 150, and 200 g; the survival rate of piglets would increase to 85.6%, 86.6%, and 87.6%, respectively; and time to reach 100 kg would decrease from 178.7 d to 176.1 d, 174.5 d, and 172.9 d, respectively [ 14 ]. Another study has also demonstrated that the lower littermate weight was associated with higher mortality [ 15 ].…”
Section: Discussionmentioning
confidence: 99%